PENERAPAN PEMANFAATAN SISTEM INFORMASI MANAJEMEN PADA PROSES PEMBELAJARAN APLIKASI GOOGLE CLASSROOM : Studi Kasus SMK Negeri 2 Majene Kec. Banggae, Kab. Majene Prov. Sulawesi Barat - Nurhusain; Damopolii, Muljono; Hasan, Mardiah (Department of Islamic Education Management, 2023)
The purpose of this study is to analyze the application of Management Information System (SIM) in the learning process at SMK Negeri 2 Majene. The research method used is qualitative research with data collection techniques through interviews and observations. The results showed that the implementation of management information systems at SMK Negeri 2 Majene has had a positive impact on the learning process. Management information systems help in the management of student information, lesson schedules, and school administration. In addition, the system also allows teachers to provide more effective feedback to students and parents through the e-learning system. The main supporting factors of implementing management information systems are school management support and cooperation between teachers and administrative officers. On the other hand, inhibiting factors are the lack of understanding of management information systems by teachers and the difficulty in integrating these systems into their learning process. Therefore, it is recommended that training and mentoring be provided to teachers in using management information systems effectively.